Efeitos da aplicação de manganês no crescimento, na nutrição e na produção de matéria seca de plantas de Brachiaria brizantha (cv. MG4) em condições de casa de vegetação - Puga, Aline Peregrina; Prado, Renato de Mello [UNESP]; Melo, Danilo Mesquita [UNESP]; Guidi, Isabella Mazer [UNESP]; Ortega, Kamilla [UNESP]; Cardoso, Saulo Strazeio [UNESP]; Almeida, Thiago Batista [UNESP] (My University, 2012)
A fertilizer with micronutrients, such as manganese in tropical forage grasses, helps to meet the nutritional requirements of both, plants and animals. The objective of this work was to study the effects of applying manganese in growth, nutrition and dry matter production of plants of Brachiaria brizantha (Hochst. ex A Rich.) Stapf in greenhouse conditions. For this, an experiment was conducted in the FCAV/UNESP, Jaboticabal, Brazil. Brachiaria brizantha plants were cultivated in pots containing 3,5 dm3 filled with samples of an Oxisol (Mn: 0,6 mg dm-3). The experimental design was completely randomized design with five treatments that corresponded to doses of manganese (0, 15, 30, 60 and 120 mg dm-3) and four replications. We evaluated the variables of growth, forage mass production, content and accumulation of Mn in the shoot in two cuts of the forage, the first, 35 days after transplanting and the second, 30 days after the first. The applied doses of manganese increased the concentration of this micronutrient in soil and plants, and the mass production of fodder in the first cut. The Brachiaria brizantha cv. MG4 has a high tolerance to manganese reaching high levels of Mn in the shoot without causing visual symptoms of toxicity.
Effects of manganese on growth, nutrition and dry matter production of plants of Brachiaria brizantha (cv. MG4) in greenhouse conditions
Keywords: Brachiaria brizantha (Hochst. ex A. Rich.) stapf; Micronutrients; Mineral nutrition; Mn; Nutritional disorder